1999
DOI: 10.1253/jcj.63.752
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery After Coronary Artery Bypass Grafting in Patients With Severe Left Ventricular Dysfunction and Preserved Myocardial Viability in the Left Anterior Descending Arterial Territory as Assessed by Thallium-201 Myocardial Perfusion Imaging

Abstract: he prognosis of patients with coronary artery disease and severe left ventricular (LV) dysfunction is poor, unless significant functional recovery is gained with coronary revascularization to viable myocardium. [1][2][3][4][5][6][7][8] The purpose of the present study was to evaluate the clinical significance of myocardial viability in the territory supplied by the left anterior descending artery (LAD) in patients with severe LV dysfunction (ejection fraction (EF) ≤35%) who underwent coronary artery bypass gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Evidence of viability in the LAD territory warrants the use of a left internal mammary artery‐to‐LAD graft for optimal benefits and provides a justification against the risks of CABG, especially in patients with longer life expectancy. A study [ 48 ] using thallium‐201 SPECT perfusion imaging indicated that in patients with severe LV dysfunction (LVEF ≤ 35%), myocardial viability in the LAD territory predicts a significant postoperative improvement in functional class and LVEF of at least 10% or more after CABG with severe LV dysfunction. Yang et al [ 22 ] agree that the number of scar segments, total scar score, and the number of scar segments in LAD territory correlated very well with LVEF after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of viability in the LAD territory warrants the use of a left internal mammary artery‐to‐LAD graft for optimal benefits and provides a justification against the risks of CABG, especially in patients with longer life expectancy. A study [ 48 ] using thallium‐201 SPECT perfusion imaging indicated that in patients with severe LV dysfunction (LVEF ≤ 35%), myocardial viability in the LAD territory predicts a significant postoperative improvement in functional class and LVEF of at least 10% or more after CABG with severe LV dysfunction. Yang et al [ 22 ] agree that the number of scar segments, total scar score, and the number of scar segments in LAD territory correlated very well with LVEF after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Chikamori et al reported that myocardial viability observed on 201 Tl SPECT perfusion imaging predicts a significant improvement in left ventricular (LV) function after CABG in patients with severe LV dysfunction. 16 Tamaki et al reported a high concordance for the stress perfusion scores between the 2 radiopharmaceuticals; reversible perfusion abnormalities were similar between stress-rest tetrofosmin and stress-delayed 201 Tl studies. 17 Stress tetrofosmin perfusion tomography is a valuable method for detecting CAD and assessing tissue viability, with an accuracy similar to that of stress 201 Tl tomography.…”
Section: Imaging Protocolmentioning
confidence: 93%
“…Chikamori et al [59] followed 100 patients, all of whom had left anterior descending territory viability, by 201 Tl stressinjection or rest-redistribution. The majority of these patients had left main or three-vessel disease.…”
Section: Improvement Of Symptomsmentioning
confidence: 99%